2019
DOI: 10.21037/qims.2019.10.05
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in glucoCEST MR body imaging at 3 Tesla

Abstract: Background: The aim of this study was to translate dynamic glucose enhancement (DGE) body magnetic resonance imaging (MRI) based on the glucose chemical exchange saturation transfer (glucoCEST) signal to a 3 T clinical field strength. Methods: An infusion protocol for intravenous (i.v.) glucose was optimised using a hyperglycaemic clamp to maximise the chances of detecting exchange-sensitive MRI signal. Numerical simulations were performed to define the optimum parameters for glucoCEST measurements with consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 29 publications
3
37
0
1
Order By: Relevance
“…Consequently, at the higher magnetic field strength of 7 T a detectable difference between the two doses was observed, whereas at lower magnetic field strength (3 T), a clear difference between the two doses was not detected. A similar decrease in the theoretically achievable glucoCEST contrast between 7 T and 3 T was recently reported from simulated data in a tumour-like tissue 21 and a small if not elusive CEST contrast was detected in cancer patients following glucose administration at 3T 38,39 . Our results are in line with those reported in literature, despite the different experimental conditions (including B0 field, B1 saturation level and duration, administration route and doses, as well as image analysis) hamper any clear comparison among studies and between molecules.…”
Section: Discussionsupporting
confidence: 83%
“…Consequently, at the higher magnetic field strength of 7 T a detectable difference between the two doses was observed, whereas at lower magnetic field strength (3 T), a clear difference between the two doses was not detected. A similar decrease in the theoretically achievable glucoCEST contrast between 7 T and 3 T was recently reported from simulated data in a tumour-like tissue 21 and a small if not elusive CEST contrast was detected in cancer patients following glucose administration at 3T 38,39 . Our results are in line with those reported in literature, despite the different experimental conditions (including B0 field, B1 saturation level and duration, administration route and doses, as well as image analysis) hamper any clear comparison among studies and between molecules.…”
Section: Discussionsupporting
confidence: 83%
“…However, the high rate of hydroxyl‐water exchange hinders CESL and CEST application of glucose and analogs at lower fields. Recent studies at 3 T have shown that it is difficult to detect tumor contrast in human patients using 25 g of glucose with CEST, 44 and the sensitivity is weak with CESL 45 . Compared to glucose, xylose‐CESL has about 70% higher area under the curve using the same dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these results suggest that GlucoCEST could represent a valid alternative to FDG-PET for tumor diagnosis and staging, still several limitations, including reduced detectability at low field and origin of the glucose-based contrast arising from different compartments need to be tackled in the next years (77).…”
Section: Imaging Glucosementioning
confidence: 90%